As festas da abolição: Comemorando o 13 de Maio de 1888 em São Luís. - MENDES, Silvan Sousa (2021)
The present study focuses on the analysis of the Abolition parties that were organized and implemented after May 13, 1888 in the city of São Luís. For this purpose, we conducted a bibliographical and documentary research in the newspapers Pacotilha, Diário do Maranhão and O Paiz , which circulated in São Luís in the second half of the 19th century, in addition to Requirements from the President of the Province located in the book entitled Various Objects, they were addressed to representatives of various institutions in order to continue the organization of the celebrations. The first step was to locate the Abolition parties in the writing of Brazilian and Maranhense history, then to better size these parties we first mapped them out in the sources, paying attention to groups and institutions that had some kind of direct or indirect involvement. The peculiarities of São Luís are taken into account, as its political, economic and social characteristics singularize its experience with Abolition. The subjects, groups and institutions present models of interpretation of what the extinction of the servile element in this city would have meant. We will know how the parties unfolded and who these subjects are through brief biographical notes and what the possible meanings were being attributed to this moment of rupture in the history of Brazil.